2010
DOI: 10.1177/0883911509360735
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin Loaded Magnetic Chitosan Nanoparticles as Multifunctional Nanocarriers

Abstract: Iron oxide (Fe3O4) containing magnetic chitosan nanoparticles were prepared with Concanavalin-A and Bleomycin as multifunctional nanocarriers for the targeted cancer therapy by co-precipitation techniques. The chemical structures of nanoparticles were analyzed by FTIR and the magnetic properties of the nanoparticles were evaluated by electron spin resonance technique and vibrational scanning mangnetometer measurements. The in vitro release profiles of Bleomycin were investigated and chitosan nanoparticles char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…For example, nano-iron has super paramagnetic properties, whereas macro-iron shows only ordinary magnetic properties (40). Nanotechnology plays an important role in different unique ways and has applications in various areas of medicine, as well as biotechnology and agriculture (41).…”
Section: Nanotechnologymentioning
confidence: 99%
“…For example, nano-iron has super paramagnetic properties, whereas macro-iron shows only ordinary magnetic properties (40). Nanotechnology plays an important role in different unique ways and has applications in various areas of medicine, as well as biotechnology and agriculture (41).…”
Section: Nanotechnologymentioning
confidence: 99%
“…cDDP-containing nanoparticles were found to be more cytotoxic in resistant and native A2780 cells. Other studies have also reported the release of cisplatin from magnetic nanoparticles [140,141] and other drugs, including bleomycin [142], concanavalin A [142], cyclophosphamide [143] and gemcitabine [144]. …”
Section: Clinical Aspects Of Thermal Potentiation Of Chemotherapeuticmentioning
confidence: 99%
“…So far, several studies have investigated PEGylation of chitosan to improve its affinity to water and organic solvents. Magnetic chitosan nanoparticles, as multifunctional nanocarriers, were loaded with bleomycin and proved to be a very effective as targeting system by Kavaz, Odabas, Güven, Demirbilek, and Denkbas (2010). PEG is a synthetic polymer approved by the FDA for internal consumption and injection in a variety of foods, cosmetics, and drug delivery systems (Cavalla, 2001).…”
Section: In Pharmaceuticsmentioning
confidence: 99%